2017
DOI: 10.18203/2320-6012.ijrms20171240
|View full text |Cite
|
Sign up to set email alerts
|

Prescription pattern of antibiotics in respiratory disorders in a tertiary care teaching hospital in Eastern part of India

Abstract: Background: Respiratory infections are increasing globally with parallel increase in world population, pollution, urbanization, overcrowding, global warming and poverty. Multi drug resistant virulent bacteria are growing very rapidly. The objective of this study was to know the prescribing pattern of antibiotics in hospitalized patients suffering from different common respiratory disorders.Methods: This was a retrospective and observational study. Data was captured from 1st January 2016 to 31st December 2016 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Upon comparing with other studies, variable results were noted. EML prescribing was higher (53%-81%) in other studies from the same region 10,11 ; while in different parts of the country it ranged from 23% to 91% (Table 8). [12][13][14] In international studies, proportion of drugs prescribed from EML were found to be higher in countries like Pakistan (98.8%), Ghana (97%), and Ethiopia (96.6%), 6,15,16 whereas a study conducted in China reported relatively lower value (48.85%).…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…Upon comparing with other studies, variable results were noted. EML prescribing was higher (53%-81%) in other studies from the same region 10,11 ; while in different parts of the country it ranged from 23% to 91% (Table 8). [12][13][14] In international studies, proportion of drugs prescribed from EML were found to be higher in countries like Pakistan (98.8%), Ghana (97%), and Ethiopia (96.6%), 6,15,16 whereas a study conducted in China reported relatively lower value (48.85%).…”
Section: Discussionmentioning
confidence: 79%
“…Similar studies conducted in this region as well as across the country have shown the mean number of medicines to be ranging between 2.91 and 4.4 as shown in Table 8, 10,[12][13][14] though one study conducted in the city showed lesser average number of drugs. 11 The average number of drugs prescribed has also been found to be higher than the recommended WHO value in many other developing countries like Ghana, Nigeria, Pakistan, Egypt (2.8-4.8). [5][6][7]15 Very few studies have reported values within recommended limits.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations